The Art of Performance : Palazzo Grassi Venice August 1979. - Hulten, Pontus; Glusberg, Jorge; Battcock, Gregory; University New York (Buenos Aires : CAYC - Centro de Arte Y Comunicacion., 1979)
Gerz, Jochen ; Kaprow, Allan ; Otth, Jean ; Pane, Gina ; Klaus, Gaetano ; Murangoni, Federica ; Orlan ; Clareboudt, Jean ; McLean, Bruce ; Haxton, David ; Kahlen, Wolf ; Weiss, Pola ; Kubota, Shigeko ; etc.
The Art of Performance, Palazzo Grassi Venice, Colloquium, 8 - 10 August 1979 ; Performances, August 8 - 12, 1979
Frans & Engels
boek